Implementasi Deep Learning dalam Pembelajaran Tari Topeng Getak Berbasis TikTok di SMP Negeri 3 Pamekasan - Roro Jamila; Setyo Yanuartuti; Anik Juwairiyah; Indar Sabri (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aims to examine the application of the concept of deep learning based on mindful, meaningful, and joyful learning in learning Topeng Getak Dance at the Junior High School (SMP) level by utilizing the TikTok application as an interactive learning medium. Facing the challenge of attracting the interest of the younger generation to traditional arts, this approach offers a conscious, meaningful, and enjoyable learning experience. Through the use of TikTok as a creative medium, students are invited to actively explore dance movements in the form of videos, reflect on the meaning in each type of movement, and enjoy the learning process interactively. This study uses a descriptive qualitative method with observations, interviews, and documentation of junior high school students. The results of the study indicate that the application of the mindful-meaningful-joyful learning strategy based on TikTok can increase student engagement, understanding of cultural values, and strengthen the preservation of Topeng Getak Dance among the younger generation. These findings emphasize the importance of technology-based innovation in developing art learning models that are relevant to the digital era.